IMPLEMENTATION OF STEAM LEARNING IN CHILDREN AGED 5-6 YEARS AT TALENTA TK SEMARANG (BELIA: Early Childhood Education Papers, 2022)
STEAM learning explores creative thinking using a child-centred approach that includes technology-based learning and problem-solving. This study discusses the implementation of STEAM learning in children aged 5-6 years at Talenta Kindergarten Semarang. This study aims to determine the implementation of STEAM learning on children aged 5-6 years at Talenta Kindergarten Semarang. The research method uses descriptive qualitative research with a case study approach. The techniques for collecting data are interviews, observation, and document review. The data analysis technique goes through several stages: data collection, documentation, data reduction, presentation, and verification. This study aims to determine the implementation of STEAM learning in Talenta Kindergarten. The data subjects are the Principal, Kindergarten B Teachers, Parents, and Children. The source of data in this research is based on a document review by looking at the process of learning planning, namely RPPM and RPPH. The results in this study include the following: a) STEAM learning planning for children aged 5-6 years at Talenta Kindergarten Semarang, namely the preparation of learning plans carried out by teachers, b) Implementation of STEAM learning for children aged 5-6 years at Talenta Kindergarten Semarang by looking at the teacher's learning and stimulation of ABK using loose parts, and c) The advantages and disadvantages of STEAM learning which shows that STEAM learning has advantages and disadvantages when applied to children with special needs (ABK) so that proper stimulation is needed. Researchers hope that the implementation of STEAM learning in Talenta Kindergarten can follow children's needs and the expected learning objectives. Keywords: Learning Planning, Learning Implementation, Inclusion, STEAM